Integrating oceans into climate policy: Any green new deal needs a splash of blue. Issue 5 (21st April 2020) - Dundas, Steven J.; Levine, Arielle S.; Lewison, Rebecca L.; Doerr, Angee N.; White, Crow; Galloway, Aaron W. E.; Garza, Corey; Hazen, Elliott L.; Padilla‐Gamiño, Jacqueline; Samhouri, Jameal F.; Spalding, Ana; Stier, Adrian; et al.
Abstract: Recent warnings from scientists suggest there is limited time to enact policies to avert wide‐ranging ecological and social damage from climate change. In the United States, discussions about comprehensive national policies to avert climate change have begun, with "Green New Deal" proposals and climate plans put forth by members of Congress and presidential candidates. Oceans are largely absent or separate from these nascent policy proposals. Here, we highlight a policy framework to develop terrestrial and ocean‐integrated policies that can complement and enhance terrestrial‐focused initiatives focused on four specific sectors: 1) energy; 2) transportation; 3) food security; and 4) habitat restoration. Given political friction and constrained budgets, an integrated policy framework offers greater potential to achieve a portfolio of mitigation and adaptation goals in a cost‐effective manner, beyond what could be realized with marine or terrestrial policy solutions alone.